KEMAMPUAN PSIKOLOGIS ANAK DENGAN TULISAN TANGAN BURUK - Andayani, Budi (Faculty of Psychology, Universitas Gadjah Mada, 2001)
Handwriting is a point to be scored in evaluating students’ achievement. For the elementary school students still learning to write this matter should not be ignored particularly in the Bahasa Indonesia subject. Cursive writing is to be mastered when a student enters his third grade and such writing would be useful until adulthood. However, this type of writing is found difficult to many students, even to those of the higher level education.The purpose of the present research is to explore psychological abilities of children with illegible handwriting that the basic problem of such children can be identified. The subjects were 3 third-grade students whose handwriting were rated as illegible by some teachers, and 1 student whose handwriting was not rated asillegible as a comparison. The Wechsler Intelligence Scale for Children and the Bender-Gestalt test were administered. The data of WISC then were presented in profiles of some cognitive abilities. Indications of brain injury and emotional disturbance could be derived from the Bender-Gestalt test. The profile of each subject showed that there is no specific tendency of cognitive abilities, and no indication of brain injury and emotional disturbance.It is concluded that the illegibility of the subjects’ handwriting is merely the case of motor skill. The illegibility of handwriting has nothing to explain the students’ academic achievement since their academic achievements, except for one subjectwhose intelligence is below average, are satisfying.